Transverse cervical vessels as a recipient site for microvascular reconstruction in vessel-depleted necks: a safe option. (December 2021) - Schettini, Adriano-Valerio; Modarressi, Ali; Ruegg, Eva; Kalbermatten, Daniel; Pittet-Cuenod, Brigitte
SUMMARY: Background: Free flap reconstruction is the gold standard in complex head and neck reconstruction. The branches of the external carotid vessels (ECVs) are considered the most suitable recipients, but they may be unavailable in patients presenting "frozen necks" or "vessel-depleted necks" due to previous treatments. We report our experience using the transverse cervical vessels (TCV) in these situations. Methods: Retrospective chart review of microsurgical head and neck reconstructions from 2005 to 2017. We focused our analysis on secondary procedures and compared the complication rate according to whether the TCV or the ECVs were used. Results: A total of 97 free flaps were performed for secondary procedures in 89 patients, mainly due to oncological recurrence and fistulae. TCV were used in 14 procedures when external carotid vessel branches were unavailable. The overall complication rate (all grade III Dindo-Clavien) was of 21% versus 35%, respectively, in the TCV and ECVs group. Grade IIIb Dindo-Clavien complications, i.e., microsurgical complications (10%) and flap loss (1%), were only recorded in the ECVs group. Other complications recorded were seroma (7% versus 1%) and hematoma (17% versus 6%) in the TCV and ECVs groups, respectively, and corresponded to grade IIIa Dindo-Claviens. Conclusions: The use of TCV is a safe second-line recipient site for microsurgical head and neck reconstruction in vessel-depleted necks. Major advantages are their anatomical position outside the previous surgical and radiation zone, lower affinity for atherosclerotic damage, and similar diameter to the pedicles of the most used flaps.